A Singly-Fed Dual-Band Microstrip Antenna for Microwave and Millimeter-Wave Applications in 5G Wireless Communication - Guo, Yu Qing; Pan, Yong Mei; Zheng, Shao Yong; Lu, Kai (IEEE transactions on vehicular technology, 2021)
The coexistence of microwave (MW) and millimeter wave (MMW) technologies is considered as the development tendency of the future 5G wireless communication system. In this paper, a single-port, single-layer, dual-band antenna with large frequency ratio is proposed to support the MW and MMW applications. This antenna mainly consists of a stub-loaded microstrip line in the center, two slot-loaded rectangular patches on the lateral sides, and two thin microstrip lines in-between which connect the former two. The stub-loaded microstrip line works as a series-fed MMW linear array at 26 GHz, and simultaneously it serves as the feed line for the MW patches operating at 4.85 GHz. The connection lines are elaborately designed to isolate the MW patches from the MMW signal, guaranteeing the radiation performance of the antenna at the two bands without requiring complicated filter. For verification, a prototype is fabricated and measured. The measured results show that the antenna has an impedance bandwidth of 3.1% and a peak gain of 8.93 dBi at the 4.85-GHz MW band, while an impedance bandwidth of 19% and a peak gain of 13.57 dBi at the 26-GHz MMW band.